America's Progressive Army: How the National Guard grew out of Progressive Era Reforms - Margis, Matthew (2016)
The National Guard has been an integral piece of the American military structure since its creation in 1903, and the Guard can trace its lineage to the colonial era. While the Guard had its origins in the old militia system, by the onset of the Spanish-American War, the militia proved to be unable to meet the twentieth century’s military challenges. Due to outdated laws and a poor public perception, the federal government instituted a series of legal actions designed to replace the militia with a more effective equivalent, beginning with the Militia Act of 1903 and ending with the National Defense Acts of 1916 and 1920. This dissertation argues that Progressive Era politicians created the National Guard within the context of Progressive reform efforts geared toward efficiency and centralization. The new National Guard’s first test as a unified military entity took place along the Mexican border in 1916, and the Guard had its chance to prove its mettle in the trenches of the First World War. Furthermore, the National Guard serves as a laboratory through which to better understand American society during the Gilded Age and Progressive Era, and military attitudes closely mirrored civilian attitudes, and illustrated the emerging class consciousness among the new middle class. This middle-class mindset drove Progressive reform efforts and culminated in the National Guard’s coalescence into a functional and effective military force